2017
DOI: 10.1186/s12891-017-1736-5
|View full text |Cite
|
Sign up to set email alerts
|

Fibroma of tendon sheath around large joints: clinical characteristics and literature review

Abstract: BackgroundFibroma of tendon sheath (FTS) is a benign tumor arising from the synovium of the tendon sheath that occurs mostly around small joints such as the fingers, hands, and wrist. However, FTS rarely arises around a large joint (knee, shoulder, elbow, and ankle) with intra-articular or extra-articular involvement. The clinical characteristics of FTS arising around a large joint are unclear. An additional 3 cases of FTS arising around a large joint are presented. Furthermore, the published cases and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 33 publications
0
44
0
8
Order By: Relevance
“…5 of the patients underwent arthroscopic tumor resection. Cases with tumors larger than 3 cm tended to be resected by open surgery, and there were no recurrences after surgery in either group [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 of the patients underwent arthroscopic tumor resection. Cases with tumors larger than 3 cm tended to be resected by open surgery, and there were no recurrences after surgery in either group [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In certain instances, local bony erosion has been noted [ 4 ]. A recent review of the literature summarized the reported cases of this condition arising in and around larger joints [ 5 ]; however, to the best of our knowledge, it has never been described within the hip joint. In the current case presentation, this benign tumor was found to be the source of severe hip pain.…”
Section: Introductionmentioning
confidence: 99%
“…Re-excision is usually curative. No metastatic case has been reported in literature (Fischer 2011;Folpe and Inwards 2010;Suzuki et al 2017).…”
Section: • Outcomementioning
confidence: 99%
“…The main differential diagnoses are with superficial fibromatoses, benign fibrous histiocytoma, nodular fasciitis, giant cell tumor of tendon sheath, and collagenous fibroma/desmoplastic fibroblastoma (Fischer 2011;Folpe and Inwards 2010;Sciot and Dal Cin 2013;Suzuki et al 2017).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Fibromas are benign tumors that can arise from the synovium of a tendon sheath, and usually occur around smaller joints such as the fingers or toes. These lesions are well circumscribed and lobulated, and histologically show presence of elongated thin-walled vessels or clefts, called slit-like spaces [5].…”
mentioning
confidence: 99%